Algorithmic Faith: Religion, AI, and Polarization in India - Raj, Preeti (Journal of Neonatal Surgery, 2025)
Religion in India now unfolds on screens and feeds. Digital media and AI shape how people pray, learn, and belong. Platforms turn sermons, rituals, and symbols into constant, public content. Algorithms decide reach and visibility, not priests or scholars. Emotional posts travel faster than balanced dialogue. Echo chambers harden group lines and mute dissent. Rumors and edited videos can spill into street violence. AI apps answer spiritual questions yet lack moral duty. Datafication tracks devotion and predicts behavior. Political actors use faith content to mobilize voters. Minority voices face trolling, bias, and erasure. Gender and caste also shape who is heard online. Digital religion strains constitutional values and civic trust. Ethical design, fair laws, and media literacy can help. Interfaith work and transparent AI offer further guardrails. The study uses qualitative methods to map these shifts. Evidence comes from digital ethnography, discourse analysis, interviews, and cases. Findings explain how platforms, code, and power remake religion today..